Analisis Hukum terhadap Matinya Satwa yang Dilindungi di Medan Zoo - Farhan Chairis; Asliani Asliani (Dinasti Review Publisher, 2024)
The total number of remaining animals at Medan Zoo is 115-116 from the initial total of 250 animals there. Medan Zoo still gets income from Medan Zoo entrance tickets and so far Medan Zoo still has donors who help financially at Medan Zoo, but Medan Zoo's finances are often not sufficient because Finances must also be divided to provide wages to employees and the need for animal feed there is also high. Regulations regarding these animals are regulated in Minister of Environment and Forestry Regulation Number 20 of 2018 concerning Protected Types of Plants and Animals, namely animals whose existence is rare and therefore protected by various regulations. Killing wild animals is an act that violates the provisions contained in Law Number 5 of 1990 concerning Conservation of Biological Resources and Ecosystems. Where in article 21 paragraph (2) (a) it is stated that it is prohibited to kill protected animals. In the results of an interview with Mr. Ahmad, the management team at Medan Zoo. The current obstacle at Medan Zoo is that there is no veterinarian who carries out health observations on the animals. at the Medan Zoo. The condition of Medan Zoo itself is categorized as quiet with 50 visitors on weekdays and 100-200 visitors on holidays. Currently, Medan Zoo receives assistance from donors and legally Medan Zoo enforces animal protection according to applicable laws. The Medan Zoo management hopes that Medan residents will be busy visiting Medan Zoo again and introducing Medan Zoo to local residents. Medan Zoo itself has been repeatedly threatened with closure, but so far Medan Zoo is still able to operate. Medan Zoo managers always think hard about keeping the animals from fasting.